Infographic. Successful hosting of a mass sporting event during the COVID-19 pandemic - Hagemann, G.; Hu, C.; Al Hassani, N.; Kahil, N. (British Journal of Sports Medicine, 2021)
In a previous BJSM blog posted in April this year Nitin K Sethi posed the question, `Amid the COVID-19 pandemic should combat sports events be held `behind closed doors"? The article`s conclusion was that with the right preparation and `by adopting some of the above practices a cautious start to combat sports events can be contemplated`. Within this context, the Ultimate Fighting Championship (UFC) elected to hold a series of fights on Yas Island, Abu Dhabi, hosted by the Department of Culture and Tourism and in close liaison with the Department of Health, from 01 to 31 July 2020. According to the WHO Mass Gatherings Risk Assessment COVID-19 Tool, the risk of hosting the event during that time (during the active phase of the pandemic) was considered `Very High Risk`.2 3 The decision then to go ahead was one that was not taken lightly, but the event organisers were confident that they could take the right measures, with a strong operational plan, to successfully protect all involved in a city that was particularly well resourced and already effectively dealing with the pandemic at a population level